Anser this question and send me the solved Anser pic
Attachments:
![](https://hi-static.z-dn.net/files/d09/81508a2c5cc97990d3473afbbcf6ad81.jpg)
Answers
Answered by
1
if it helps you then please mark as brainliest
Attachments:
![](https://hi-static.z-dn.net/files/d5a/b5c53bcce08bfa364cd9919ff169a416.jpg)
Ritikraj828:
my answer is right please tick as brainliest
Answered by
0
Hi,
(2√2+3√3) (2√2-3√3)
(a+b)(a-b) = (a²- b²)
[(2√2)²-(3√3)²]
= [(4 x 2) - (9 x 3)]
= (8 - 27) = -19
hope it helped u!!
(2√2+3√3) (2√2-3√3)
(a+b)(a-b) = (a²- b²)
[(2√2)²-(3√3)²]
= [(4 x 2) - (9 x 3)]
= (8 - 27) = -19
hope it helped u!!
Similar questions
Math,
9 months ago
Computer Science,
9 months ago
English,
9 months ago
World Languages,
1 year ago
Math,
1 year ago
Social Sciences,
1 year ago
Physics,
1 year ago